Cancer‐Specific health equity metrics in the United States of America: A scoping review - Angela Starkweather; Bevin Cohen; Tamryn F. Gray; Lauri Linder; Noah Zanville (Cancer Medicine, 2023)
Abstract Health disparities in cancer care persist, and in some cases are growing, despite decades of research aimed at achieving equal outcomes for all Americans. There is growing consensus that reducing disparities will require a shift from aiming to provide care that is equal, to aiming to provide care that is equitable. The current landscape of metrics and interventions that move beyond equality (i.e., care provided equally to all patients) and towards equity (i.e., care provided variably and justly such that patients achieve equal outcomes) have not been characterized. Thus, the aim of this scoping literature review was to identify cancer‐specific health equity metrics and interventions, and to explore current gaps in the field. Following PRISMA guidelines, PubMed, CINAHL, PsycInfo, and Scopus were searched for studies published in English between 2012 and 2022 that implemented a metric to identify or an intervention to address cancer care inequities in the United States. The search returned 36,724 unique articles, of which 40 articles (1%) included an intervention to advance health equity. Metrics included timeliness of screening and treatment, receipt of goal‐concordant care, and survival. The vast majority of articles were cross‐sectional or cohort studies that described health disparities using one or more outcome metrics. Gaps identified included research on receipt of guideline‐concordant care, interventions addressing multiple levels of structural and social determinants of health, inclusion of children and families, and patient‐reported outcomes or other sources of data that could help inform interventions to advance equity.